Pengembangan Teknologi GeoNode Sebagai Geoportal Tata Ruang di Kota Balikpapan - Widyantoro, Bimo Aji; Pamungkas, Srirahadita (COMPACT: Spatial Development Journal, 2024)
The implementation of Geographic Information System (GIS)-based technology in urban spatial planning is increasingly important in supporting the management and proper decision-making. Effective spatial planning requires access to accurate and easily accessible spatial data. GeoNode is an open source platform for spatial data management and sharing, which can provide effective solutions in supporting digital-based spatial information systems. This study aims to develop and implement GeoNode as a supporting tool in spatial management in Balikpapan City. The methods used include spatial data collection, GeoNode infrastructure development, and integrating data from various sources. The results of the study indicate that GeoNode can improve efficiency in accessing, visualizing, and creating spatial data. GeoNode can be a reliable geoportal in providing real-time access to more inclusive spatial data. The application of GeoNode technology as a medium for sharing and disseminating spatial data can be a model for the development of spatial information systems in Balikpapan City.